(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Hirschsprung’s disease or the congenital intestinal aganglionosis is the result of arrested fetal development of the myentric nervous system, but the precise pathogenic mechanisms involved are unknown. The successful treatment of infants and children with Hirschsprung’s disease depends on prompt diagnosis and early treatment. Objective:To compare the complications of Swenson’s and Soave’s pull-through procedures for the management of Hirschsprung’s disease. Methods:This study was conducted by patient’s relative interview in Central Teaching Hospital of Pediatrics in Baghdad for the period from June 2006 to June 2010 .All the patients were under (10) years old who were admitted and underwent surgical interference and followed up under the study group. This study included 40 infants and children with Hirschsprung’s disease underwent either Swenson’s or Soave’s pull-through procedures. On average, the post operative follow-up period was six months after the last stage of operation (closure of colostomy). Results:The patients consisted of 32 males (80%) and eight females (20%), a ratio of 4:1. Their age ranged from 1 day to 10 years. History of failure to pass meconium was the commonest presentation and was found in (87.5%). Twenty-five patients (62.5%) underwent a Swenson’s pull-through and fifteen patients (37.5%) underwent Soave’s pull-through. The incidence of the complications following Swenson’s procedure was 24% while after Soave’s procedure was 20%. Wound infection and adhesive intestinal obstruction were the commonest complications after Swenson’s pull-through and occurred in (12%) while anastomatic stricture was the commonest complication after Soave’s procedure and occurred in (20%). Conclusion:The rate of complications was higher following Swenson’s pull-through in comparison to Soave’s pull- through procedure. Keywords: Hirschsprung’s disease, Swenson’s pull-through, Soave’s pull through, complications.